Final answer:
Given b: 4 1/3b+b=6b–10.4, the solution is b = -7.8
Step-by-step explanation:
To solve for b in the given equation, we will follow the steps below:
Combine like terms by adding b to both sides of the equation:
4 1/3b + b = 6b - 10.4
Combine the b terms: 4 1/3b + b = 7 1/3b
Move all b terms to one side of the equation:
7 1/3b - 6b = -10.4
Combine the b terms: 1 1/3b = -10.4
Isolate b by dividing both sides of the equation by 1 1/3:
b = -10.4 ÷ (1 1/3)
Convert the mixed fraction to an improper fraction: 1 1/3 = 4/3
Divide: b = -10.4 ÷ 4/3
Invert the denominator and multiply: b = -10.4 x 3/4
Calculate the result: b = -31.2/4 = -7.8
So therefore the solution is b = -7.8